1999
DOI: 10.1002/(sici)1097-4660(199911)74:11<1030::aid-jctb144>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Influence of phosphate and iron on the extent of calcium carbonate precipitation during anaerobic digestion

Abstract: The extent to which calcium carbonate deposition in an anaerobic reactor can be reduced by adding inhibitors (phosphate and iron) of calcium carbonate crystal growth was investigated. At several concentrations of the additive, the extent of precipitation was assessed in continuous experiments with laboratory-scale reactors. In the reactor, phosphate concentrations as low as 0.5± 5 mg total-P dm À3 were found to severely inhibit CaCO 3 precipitation. However, iron did not inhibit the deposition of CaCO 3 , whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 24 publications
3
29
0
1
Order By: Relevance
“…The CaCO 3 polymorphs in decreasing stability are: calcite, aragonite, vaterite, monohydrocalcite, ikaite and amorphous calcium carbonate (Meiron et al, 2011;Radha et al, 2010). Although CaCO 3 deposition in anaerobic reactors is commonly occurring and therefore it has been extensively studied (Langerak et al, 1999;Lier & Boncz, 2002), its interconnections with silicate mineral dissolution and biogas improvement have not been studied. In this study we have investigated the kinetics of calcium carbonate precipitation and its effects on biogas enrichment from starch fermentation and pH neutralization in an integrated AD system with wollastonite.…”
Section: Theoretical Aspectsmentioning
confidence: 99%
“…The CaCO 3 polymorphs in decreasing stability are: calcite, aragonite, vaterite, monohydrocalcite, ikaite and amorphous calcium carbonate (Meiron et al, 2011;Radha et al, 2010). Although CaCO 3 deposition in anaerobic reactors is commonly occurring and therefore it has been extensively studied (Langerak et al, 1999;Lier & Boncz, 2002), its interconnections with silicate mineral dissolution and biogas improvement have not been studied. In this study we have investigated the kinetics of calcium carbonate precipitation and its effects on biogas enrichment from starch fermentation and pH neutralization in an integrated AD system with wollastonite.…”
Section: Theoretical Aspectsmentioning
confidence: 99%
“…Hence a minimal quantity of mineral seed can be used as a default initial condition where the amount of mineral phase present is nil or unknown but small. While the model was more tolerant to high values of kcryst (indicating that it is equilibriumlimited), it is noted from Figure 3.4 and a survey of the wastewater modelling literature (Barat et al, 2011;Joss et al, 2011;van Langerak et al, 1999) that SI values for calcite/aragonite are either significantly positive or negative in wastewater, so precipitation or dissolution have not usually attained strict equilibrium, even within the timeframe of biological processes. Accordingly, it is suggested that, although the model is more tolerant to high values of kcryst, it remains kinetically limited as indicated by the non-zero SI values (Figure 3.4).…”
Section: Baseline Modelling Approachmentioning
confidence: 96%
“…As illustrated in Figure 2.4, some of the minerals of interest in wastewater treatment, in particular calcium carbonate and calcium phosphate, are capable of crystallizing out of solution in a variety of different mineral forms (crystalline vs. amorphous, and/or various crystalline polymorphs) (Barat et al 2011, Plummer and Busenberg 1982, van Langerak et al 1999. This is in agreement with the Ostwald rule of stages (Mullin 2001), which stipulates that the formation of a more stable phase is preceded by the preferential formation of one or more thermodynamically less stable precursor phases with progressive transformation into the more stable thermodynamic phase (Mullin 2001).…”
Section: Mechanisms Of Particle Growthmentioning
confidence: 99%
See 2 more Smart Citations